2014
DOI: 10.1091/mbc.e13-11-0680
|View full text |Cite
|
Sign up to set email alerts
|

MgcRacGAP interacts with cingulin and paracingulin to regulate Rac1 activation and development of the tight junction barrier during epithelial junction assembly

Abstract: The Rac1 inhibitor MgcRacGAP regulates Rac1 activation and TJ barrier development during junction assembly in epithelial cells. CGN and CGNL1 recruit MgcRacGAP to the TJ and interact with MgcRacGAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 68 publications
(101 reference statements)
2
51
0
Order By: Relevance
“…Recent work has shown that Mgc also regulates cellcell junctions in interphase epithelial cells (Breznau et al, 2015;Guillemot et al, 2014;Ratheesh et al, 2012). We observed a significant decrease in the ability of the MgcSxNN mutant to track along growing MT plus ends with EB3 when compared to MgcWT in interphase Cos-7 cells.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Recent work has shown that Mgc also regulates cellcell junctions in interphase epithelial cells (Breznau et al, 2015;Guillemot et al, 2014;Ratheesh et al, 2012). We observed a significant decrease in the ability of the MgcSxNN mutant to track along growing MT plus ends with EB3 when compared to MgcWT in interphase Cos-7 cells.…”
Section: Discussionmentioning
confidence: 52%
“…The MgcRacGAP SxIP motif is necessary for proper adherens junction structure Next, we tested whether mutating the Mgc SxIP motif affects the population of Mgc that localizes to and regulates cell-cell junctions in interphase epithelial cells (Breznau et al, 2015;Guillemot et al, 2014;Ratheesh et al, 2012). Constructs were injected so as to generate mosaic embryos, such that cells expressing MO+MgcWT or MO+MgcSxNN could be compared with neighboring control cells.…”
Section: Mutation Of the Mgcracgap Sxip Motif Disrupts Equatorial Accmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise localization of activated RhoA and Cdc42 in polarized epithelial cells is still unclear, an apical-basal gradient of Rac1 activity has been observed with higher Rac1 activity at more basal regions due to the localized activation of the RacGEF TIAM1, which is required for proper junction formation (Mack et al, 2012). Consistent with this, MgcRacGAP localizes and acts apically (Guillemot et al, 2014). Collectively, the studies support a key role for the precise spatio-temporal activation of Rho family GTPases in junction formation and epithelial organization.…”
Section: The Activation Of Rho Family Gtpases Is Spatio-temporally mentioning
confidence: 81%
“…Alternatively, Rich1 is released from Amot by competitive binding of the Merlin/NF2 tumor suppressor, leading to a reduction of local Rac1 activity (Yi et al, 2011). Other means to suppress apical Rac1 activity are through the junctional male germ cell (Mgc) Rac GAP (also known as RacGAP1), which is part of the Ect2 complex, or through the Rac-specific filament Abinding GAP (FilGAP, also known as ARHGAP24), which is activated downstream of RhoA signaling and ROCK-mediated phosphorylation (Guillemot et al, 2014;Ohta et al, 2006;Ratheesh et al, 2012). Moreover, apical Rac GAP chimaerins CHN1 and CHN2 have been reported to inhibit Rac1 activity to control epithelial cyst morphogenesis (Yagi et al, 2012).…”
Section: The Activation Of Rho Family Gtpases Is Spatio-temporally mentioning
confidence: 99%